Confronting Racism to Advance Our Science. Issue 1 (25th March 2021) - Zeitler, Peter; Barros, Ana P.; Becker, Thorsten W.; Davidson, Eric A.; Ehlmann, Bethany L.; Gruber, Nicolas; Hofmann, Eileen E.; Hudson, Mary K.; Illangasekare, Tissa H.; Kang, Sarah M.; Malanotte‐Rizzoli, Paola; Moerchen, Margaret; et al.
Abstract: As individuals serving on the AGU Advances editorial board, we condemn racism, affirm that Black Lives Matter, and recognize that inequality is built into the systems that have allowed us to prosper. We aim to persistently foster discussion about racism, inequity, and the need to make our community more diverse and inclusive. This will help AGU Advances do a better job in publishing important science that inclusively reflects the ideas and contributions of all in our community. Key Points: The editorial board wishes to enable their journal to represent the Earth and space sciences community in all its diversity The board recognizes that inequality is part of systems that have allowed them to prosper and pledges to support diversity and inclusion The board will commission and take contributions to an editorial series on the nature and impact of racism and other inequities in science